2020
DOI: 10.1155/2020/5972398
|View full text |Cite
|
Sign up to set email alerts
|

Power Optimization in Mobile Robots Using a Real-Time Heuristic

Abstract: Mobile robots typically run using finite energy resources, supplied by finite batteries. The limitation of energy resources requires human intervention for recharging the batteries. To reduce human intervention, this work focuses on coordinating power in a group of robots. A power optimization subroutine provides some sense of distribution of power by the control unit (CU). A variety of on-board sensors, actuators, and communication modules are controlled by a heuristic-based controller class allowing such com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Therefore, it is necessary to first identify and estimate the power consumption of the platform's various hardware components. Subsequently, the power associated with software applications needs to be modeled, since different heuristics would produce other levels of power consumption [29].…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to first identify and estimate the power consumption of the platform's various hardware components. Subsequently, the power associated with software applications needs to be modeled, since different heuristics would produce other levels of power consumption [29].…”
Section: Challengesmentioning
confidence: 99%
“…During the experiments, we observed that a demo is highly dependent on depth information or detection services, which constitute the robot's baseline energy consumption. In addition, in light of the economic aspects discussed in the following section, it is advisable to address sustainability issues already when designing demonstration routines [29].…”
Section: Developing Energy-efficient Demosmentioning
confidence: 99%
“…for σ = 0 (38) where σ = β(e 2 ) = υ r − e 2 for e 2 = 0 0 for e 2 = 0 (39) and α 0 (σ) follows from Equation (20).…”
Section: Lemmamentioning
confidence: 99%
“…While much effort has been devoted to energy modelling, power conservation, and optimization techniques [38,39] for precise tracking of WMRs, to the best of the author's knowledge, there has been to date little or no attention given towards investigating the effects of the power supply variation on the model's parameters. The main contribution of this work is on enhancing the tracking performance of a WMR, which is driven by two DC motors that are subject to structural model errors that are induced by time-varying power supply as well as behaviour of motions and motor speed.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 summarizes the battery-discharging times until the voltage drops to 8.5 V for both hard and soft surfaces, the three walking speeds and the still-standing condition. The measured battery-discharge time [30] is expressed in the form…”
Section: Battery-voltage-measurement Circuit (Bvmc)mentioning
confidence: 99%